Helmuth von Moltke and the origins of the First World War - Mombauer, Annika 1967- (New studies in European history, 2001)
"The book takes specific issue with the common perception of Moltke as an ineffectual and reluctant military leader, remembered primarily for the defeat at the Battle of the Marne and his alleged adulteration of the Schlieffen Plan. It concludes that, on the contrary, he was both bellicose and ambitious, hoping for war 'the sooner the better' and playing a crucial role in the outbreak and early months of the First World War."--Jacket